The Effect of Service Quality and System Quality on Online Registration Aplication on User Satisfaction with Usage Frequency as An Intervening Variable - Pratama, Erlan Anugrah; Rasyid, Harun Al (Accounting Department,, 2024)
Purpose — This research aims to investigate the impact of system quality and service quality on user satisfaction, specifically examining the mediating role of usage frequency in an online registration information system for hospital queues. Design/methodology/approach — This research used an analytic observational design with a cross-sectional approach. Data were collected from 96 patients attending a Private Hospital in Malang City from May to July 2022. The data were analyzed using multiple linear regression and path analysis, including the Sobel test and causal step. Findings — The results of this research indicate that neither service quality (t-test statistic = -1.458, t-stat < 1.96) nor system quality (t-test statistic = -0.448, t-stat < 1.96) directly affected user satisfaction through usage frequency. This suggests that usage frequency does not mediate the relationship between service quality, system quality, and user satisfaction. Practical implications — This research highlight the importance of service quality and system quality in online registration application services. Improving these aspects could enhance user satisfaction, even though usage frequency may not directly mediate this relationship. Originality/value — This research contributes to the understanding of factors influencing user satisfaction in online registration systems for healthcare services. The findings suggest that service providers should focus on improving system quality and service quality to enhance user satisfaction, independent of usage frequency.